Partial and Radical Nephrectomy Provides Equivalent Oncologic Outcomes in pT3a Renal Cell Carcinoma: A Population-Based Study - Tian, Jihua; Zeng, Xing; Wan, Jie; Gan, Jiahua; Ke, Chunjin; Guan, Wei; Hu, Zhiquan; Yang, Chunguang (Frontiers in Oncology, 2022)
Purpose To compare the CSS and OS of patients localized T3a RCC after partial nephrectomy (PN) or radical nephrectomy (RN). Methods We obtained the demographic and clinicopathological data of 7127 patients with localized T3a RCC and underwent PN or RN from the SEER database. These patients were divided into fat invasion cohort and venous invasion cohort for subsequent analysis. Kaplan-Meier analysis (KMA), univariate and multivariate Cox proportional hazards regression analysis were used to evaluate the effects of PN or RN on OS and CSS. Meanwhile, 65 cases with clinical T1 (cT1) RCC upstaged to pathological T3a (pT3a) that treated in Tongji Hospital (TJH) from 2011 to 2020 and underwent PN or RN were identified. Results In the study cohort, 2085 (29.3%) patients died during the 1-172 months follow-up, of which 1155 (16.2%) died of RCC. In the two cohorts of fat invasion and venous invasion, KMA indicated that PN group had favorable survival (p<0.001). However, after PSM, univariate and multivariate COX regression analysis showed that PN and RN groups had comparable CSS in the fat invasion cohort (p=0.075) and the venous invasion cohort (p=0.190). During 1-104 months of follow-up, 9 cases in the Tongji cohort had disease recurrence. There was no significant difference in recurrence-free survival between the RN group and the PN group (p=0.170). Conclusions Our analysis showed that after balancing these factors, patients with localized pT3a RCC receiving PN or RN can achieve comparable oncologic outcome. PN is safe for selected T3a patients.